The Relationship Between Lipid Profile and HBA1C Levels in Type 2 Diabetes Melitus Patients - Miako Pasinggi; Irfansyah Baharuddin Pakki; Yadi Yadi (Indonesian Journal of Global Health Research, 2025)
Diabetes Mellitus is a chronic disease with high morbidity and mortality rates, requiring comprehensive and integrated management. Dyslipidemia is an important risk factor contributing to the occurrence of both microvascular and macrovascular complications in individuals with Diabetes Mellitus. Optimal control of HbA1c levels and lipid profiles is considered essential in reducing the risk of complications and improving patient outcomes. Therefore, monitoring and managing these parameters is a critical component of diabetes care to prevent further complications. This study aims to analyze relationship between lipid profile with HbA1c levels in Type 2 Diabetes Mellitus (T2DM) patients at Puskesmas in Samarinda. A cross-sectional study was conducted involving 1,482 patients with T2DM, selected through a total sampling technique. Data were obtained from secondary sources, specifically medical records. Bivariat analysis using the Chi-Square test was performed to evaluate the relationship between lipid profile and HbA1c levels. The analysis identified significant relationship between TG (p = <0,001 ; OR = 3,350; 95% CI:2,701-4,157), TC (p = <0,001; OR = 1,862; 95% CI: 1,486-2,334), HDL-C (p = 0,003; OR = 1,567; 95% CI: 1,169-2,100), and LDL-C (p = 0,013; OR = 1,310; 95% CI: 1,063-1,614). This study found a significant association between all components of the lipid profile and HbA1c levels among patients with type 2 diabetes mellitus (T2DM) in Samarinda. Levels of triglycerides (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) were all significantly related to poor glycemic control. .